Aluminum electrolysis energy-saving copper-embedded cathode carbon block group

By designing a specific installation structure and threaded connection on the cathode carbon block and steel rod, and using a threaded pressure rod to tightly fit the copper core into the steel rod, the problem of loose fitting of the copper core in the existing technology is solved, and the Reduction in cost and energy consumption and improvement in aluminum electrolysis performance.

CN222374797UActive Publication Date: 2025-01-21ZHONGNING JIN NING ALUMINUM MAGNESIUM NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202421087514.0
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-05-17
Publication Date
2025-01-21
Estimated Expiration
2034-05-17

AI Technical Summary

Technical Problem

In the premise of reducing costs and energy consumption, it is difficult for the prior art to tightly fit the copper core into the steel rod, affecting the aluminum electrolytic performance.

Method used

By creating an installation groove on the surface of the cathode carbon block, the steel rod is embedded in it, and an embedded groove and a threaded connection groove are provided inside the steel rod. The copper core is extruded and deformed using a threaded pressure rod to fill the gap, so that the copper core and the steel rod are connected. Tight fit.

Benefits of technology

The tight fitting of the copper core within the steel rod is achieved, reducing the cost and energy consumption of the manufacturing process, improving the aluminum electrolysis performance, and simplifying the maintenance process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222374797U_ABST
    Figure CN222374797U_ABST
Patent Text Reader

Abstract

The utility model discloses an aluminum electrolysis energy-saving copper-embedded cathode carbon block group which comprises a cathode carbon block and a steel bar, a mounting groove is formed in the surface of the cathode carbon block, and the steel bar is embedded in the mounting groove; an embedding groove is formed in the steel bar, and a copper core is arranged in the embedding groove; a threaded connecting groove communicated with the embedding groove is formed in the end of the steel bar, an end cover is arranged at the end of the steel bar, a threaded sealing sleeve and a threaded pressing rod are fixed to the inner side of the end cover, and the threaded pressing rod is located in the threaded sealing sleeve; according to the cathode carbon block, the copper core is extruded and deformed through the threaded pressing rod, and the deformed copper core can be filled in a gap reserved between the copper core and the embedding groove, so that the copper core can be tightly attached to the steel bar, the normal electrolysis performance of the cathode carbon block is effectively guaranteed, and compared with copper core pouring in a high-temperature mode in the prior art, the manufacturing process is safe and time-saving, and the production efficiency is improved. And the cost and the energy consumption are lower.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of cathode carbon blocks, in particular to an energy-saving copper-embedded cathode carbon block group for aluminum electrolysis. Background Art

[0002] Cathode carbon block refers to a carbon block made of high-quality anthracite, coke, graphite, etc. It is used as the cathode of the aluminum electrolytic cell. It is built at the bottom of the electrolytic cell and is also called the bottom carbon block. Cathode carbon block is an important part of the aluminum electrolytic cell, which is beneficial to energy saving and cell life improvement in aluminum electrolysis production. In the process of large-scale aluminum electrolytic cells, the cathode rod consists of two parts, namely the cathode rod connected to the workpiece and the clip fixed to the edge of the plating tank. The cathode rod is generally composed of a copper core and a steel rod, and the cathode rod is installed in the cathode carbon block for use together.

[0003] In addition, the quality of the cathode carbon material lining the aluminum electrolytic cell directly affects the service life and power consumption of the electrolytic cell. In aluminum electrolytic production, the cathode carbon block is in direct contact with the electrolyte and liquid aluminum and is washed by them. If the quality of the cathode carbon block is not high, it will increase the content of non-metallic inclusions in the metal, thereby reducing the quality of aluminum products. At the same time, the consumption of carbon materials increases and the number of maintenance increases, resulting in worsening working conditions, reduced furnace life, and increased smelting costs. Secondly, during the preparation of the electrolytic cell, cathode rods are required at the cathode position. As an important component of electrolytic aluminum production, the cathode system has a long replacement cycle, and its conductive performance and comprehensive quality have a very important impact on the energy consumption of electrolytic aluminum production.

[0004] During the aluminum electrolysis process, since the cathode carbon block is used together with the cathode rod, and the cathode rod is composed of a copper core and a steel rod, in order to ensure that the copper core is in close contact with the steel rod, copper is often melted into copper liquid at high temperature, and the copper core is then embedded in the steel rod by pouring the copper liquid. Although this method can embed the copper core tightly in the steel rod, it requires casting equipment to complete, which is not energy-efficient, resulting in high manufacturing costs. In addition, it is necessary to wait for the copper core to cool and form, and the manufacturing time is long. If it is simply embedded in the steel rod, gaps are likely to appear between the copper core and the steel rod, resulting in a loose embedding, affecting the electrolysis performance. Therefore, for the existing technology, how to embed the copper core tightly in the steel rod while reducing costs and energy consumption still needs to be improved. Utility Model Content

[0005] In view of the deficiencies of the prior art, the utility model provides an energy-saving copper-embedded cathode carbon block group for aluminum electrolysis to solve the problems of how to tightly embed the existing copper core in a steel rod with low cost and energy consumption.

[0006] To achieve the above purpose, the utility model is implemented through the following technical solutions: an energy-saving copper-embedded cathode carbon block set for aluminum electrolysis, comprising a cathode carbon block and a steel rod, wherein a mounting groove is provided on the surface of the cathode carbon block, and the steel rod is embedded in the mounting groove;

[0007] An embedding groove is provided inside the steel rod, and a copper core is arranged in the embedding groove;

[0008] The end of the steel rod is provided with a threaded connection groove which is communicated with the embedding groove. The end of the steel rod is provided with an end cover. A threaded sealing sleeve and a threaded pressure rod are fixed inside the end cover. The threaded pressure rod is located inside the threaded sealing sleeve.

[0009] Preferably, the embedding groove and the threaded connection groove have the same inner diameter.

[0010] Preferably, the threaded pressure rod is threadably matched with the threaded connection groove.

[0011] Preferably, an annular thread sealing groove is formed at the end of the steel rod, the thread sealing groove is located at the periphery of the thread connection groove, and the thread sealing sleeve is threadably matched with the thread sealing groove.

[0012] Preferably, operation holes are formed around the periphery of the end cover.

[0013] Preferably, the cathode carbon block is made of semi-graphitized carbon.

[0014] Preferably, the end cover, the threaded sealing sleeve, the threaded pressure rod and the steel rod are made of the same material.

[0015] The utility model provides an energy-saving copper-embedded cathode carbon block group for aluminum electrolysis, which has the following beneficial effects:

[0016] 1. The copper core is squeezed and deformed by the threaded pressure rod. The deformed copper core will fill the gap left between the copper core and the embedded groove, so as to make the copper core fit the steel rod tightly. During the aluminum electrolysis process, the normal electrolysis performance of the cathode carbon block is effectively guaranteed. Compared with the copper core casting at high temperature in the prior art, this manufacturing process is safe and time-saving, and has lower cost and energy consumption.

[0017] 2. The copper core is sealed by connecting the threaded pressure rod with the threaded connection groove, and the copper core is sealed again by connecting the threaded sealing sleeve with the threaded sealing groove, which is not only conducive to achieving the double-layer sealing effect of the copper core, but also can prevent the threaded pressure rod and the end cover from loosening, thereby effectively preventing the copper core from loosening in the steel rod.

[0018] 3. By screwing the threaded pressure rod out of the threaded connection groove and screwing the threaded sealing sleeve out of the threaded sealing groove, it is convenient to replace the failed copper core, thereby effectively reducing the maintenance cost of the cathode carbon block. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of the overall structure of the utility model;

[0020] Figure 2 This is a schematic diagram of the structure of the cathode carbon block of the utility model;

[0021] Figure 3 This is a schematic diagram of the upright structure of the steel rod of the utility model;

[0022] Figure 4 This is a schematic diagram of the upright split structure of the steel rod of the utility model;

[0023] Figure 5 This is a schematic diagram of the structure of the end portion of the threaded sealing sleeve of the utility model;

[0024] Figure 6 This is a schematic diagram of the copper core embedded installation plan structure of the utility model;

[0025] Figure 7 This is a schematic diagram of the upright plane structure of the steel rod of the utility model;

[0026] Figure 8 It is a schematic diagram of the planar structure of the upright splitting of the steel rod of the utility model.

[0027] Figure 1-8 Middle: cathode carbon block 1, steel rod 2, embedding groove 3, end cover 4, threaded sealing groove 5, operating hole 6, threaded sealing sleeve 7, threaded pressure rod 8, threaded connection groove 9, installation groove 10, copper core 11. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the utility model will be clearly and completely described below in conjunction with the drawings in the embodiments of the utility model. Obviously, the described embodiments are only part of the embodiments of the utility model, rather than all of the embodiments. Based on the embodiments in the utility model, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the utility model.

[0029] See also Figure 1-8 The utility model provides a technical solution: an energy-saving copper-embedded cathode carbon block group for aluminum electrolysis, comprising a cathode carbon block 1 and a steel rod 2, wherein a mounting groove 10 is provided on the surface of the cathode carbon block 1, the steel rod 2 is embedded in the mounting groove 10, an embedding groove 3 is provided inside the steel rod 2, a copper core 11 is provided in the embedding groove 3, a threaded connection groove 9 communicating with the embedding groove 3 is provided at the end of the steel rod 2, an end cover 4 is provided at the end of the steel rod 2, a threaded sealing sleeve 7 and a threaded pressure rod 8 are fixed on the inner side of the end cover 4, the threaded pressure rod 8 is located in the threaded sealing sleeve 7, the threaded sealing groove 5 is located outside the threaded connection groove 9, and the threaded pressure rod 8 is threadedly matched with the threaded connection groove 9.

[0030] When the copper core 11 is embedded in the steel rod 2, the copper core 11 is inserted into the embedding groove 3 through the threaded connection groove 9, and an extra part of the length of the copper core 11 is reserved. The extra length of the copper core 11 extends in the threaded connection groove 9, and then the threaded pressure rod 8 is threadedly connected to the threaded connection groove 9. The threaded pressure rod 8 continuously moves downward and continuously squeezes and deforms the copper core 11. The deformed copper core 11 fills the gap left between the copper core 11 and the embedding groove 3 until the copper core 11 no longer extends into the threaded connection groove 9, that is, the copper core 11 is completely embedded in the embedding groove 3, thereby facilitating the copper core 11 to be tightly fixed. The steel rod 2 is tightly fitted to effectively ensure the normal electrolytic performance of the cathode carbon block 1. Compared with the prior art of casting the copper core 11 at high temperature, this manufacturing method is safe and time-saving, and has lower cost and energy consumption. In addition, during the aluminum electrolysis process, the steel rod 2 is inserted into the installation groove 10 of the cathode carbon block 1. Since the copper core 11 is embedded in the steel rod 2 to improve its conductivity, the pressure drop at the bottom of the furnace is reduced, the current density distribution on the cathode surface is more uniform, the horizontal current is reduced, the MHD stability is improved, and the flow rate of the aluminum liquid is reduced, which has a positive effect on the current efficiency. At the same time, the service life of the cathode carbon block 1 is increased, and the aluminum electrolysis process is more energy-efficient.

[0031] See also Figure 1 , 2 In this embodiment, a mounting groove 10 is opened on the surface of the cathode carbon block 1, and the steel rod 2 is embedded in the mounting groove 10. The cathode carbon block 1 is made of semi-graphitized carbon.

[0032] Since the cathode carbon block 1 is made of semi-graphitized carbon material, and the steel rod 2 is inserted into the mounting groove 10 of the cathode carbon block 1, a semi-graphite cathode is formed. In addition to the characteristics of the ordinary cathode carbon block 1, the semi-graphite cathode carbon block 1 also has a strong sodium corrosion resistance. The life of the aluminum electrolytic cell is mainly related to the sodium corrosion resistance of the cathode lining. Therefore, the use of the semi-graphite cathode carbon block 1 in the electrolytic cell is conducive to prolonging the life. Secondly, compared with ordinary carbon blocks, the semi-graphite cathode carbon block 1 has a smaller specific resistance, thereby reducing the furnace bottom pressure drop. If the same working voltage is maintained, the inter-electrode distance is relatively increased. Under the condition that other conditions remain unchanged, the increase in the inter-electrode distance lengthens the transfer process of dissolved aluminum from the cathode to the anode, reduces the concentration gradient of the aluminum liquid, and reduces the diffusion rate of aluminum. At the same time, the circulation and convection of the electrolyte will also be weakened, and the amount of anode gas will be reduced, which will correspondingly reduce the secondary reaction of dissolved aluminum and anode gas, reduce the loss of aluminum, and improve the current efficiency. In summary, the aluminum electrolysis process is more energy-efficient.

[0033] See also Figure 6 , 7 In this embodiment, an annular thread sealing groove 5 is formed at the end of the steel rod 2 , and the thread sealing sleeve 7 is threadably matched with the thread sealing groove 5 .

[0034] Moreover, the copper core 11 is sealed in the embedding groove 5 by the connection between the threaded pressure rod 8 and the threaded connection groove 9, and the copper core 11 is sealed again by the connection between the threaded sealing sleeve 7 and the threaded sealing groove 5 until the end cover 4 is in close contact with the steel rod 2, which is not only conducive to achieving a double-layer sealing effect on the copper core 11, but also can prevent the threaded pressure rod 8 and the end cover 4 from loosening through the double-layer threaded connection, thereby effectively preventing the copper core 11 from loosening in the steel rod 2.

[0035] See also Figure 8 In this embodiment, the inner diameter of the embedding groove 3 is equal to the inner diameter of the threaded connection groove 9.

[0036] This helps ensure that the copper core 11 is smoothly embedded in the embedding groove 3 through the threaded connection groove 9, thereby ensuring that the embedding work proceeds normally.

[0037] See also Figure 4 , 6 7. In this embodiment, operation holes 6 are formed around the periphery of the end cover 4.

[0038] When the end cover 4 drives the threaded pressure rod 8 to be tightened into the threaded connection groove 9, and the threaded sealing sleeve 7 is connected to the threaded sealing groove 5, a crowbar is inserted into any one of the operating holes 6, and then the end cover 4 is driven to rotate by the crowbar, which is conducive to easily and labor-savingly driving the threaded pressure rod 8 and the threaded sealing sleeve 7 into the threaded connection groove 9 and the threaded sealing groove 5 respectively, effectively ensuring the effect of the threaded pressure rod 8 on the extrusion deformation of the copper core 11.

[0039] See also Figure 8 In this embodiment, the threaded pressure rod 8 is threadably matched with the threaded connection groove 9 , and the threaded sealing sleeve 7 is threadably matched with the threaded sealing groove 5 .

[0040] When the copper core 11 fails and needs to be replaced, the threaded pressure rod 8 is screwed out of the threaded connection groove 9, and the threaded sealing sleeve 7 is screwed out of the threaded sealing groove 5, and then the failed copper core 11 is poured out. This facilitates the replacement of the failed copper core 11 without replacing the entire cathode rod, thereby effectively reducing the maintenance cost of the cathode carbon block 1.

[0041] See also Figure 7 In this embodiment, the end cover 4, the threaded sealing sleeve 7, the threaded pressure rod 8 and the steel rod 2 are made of the same material.

[0042] Since the end cover 4, the threaded sealing sleeve 7, the threaded pressure rod 8 and the steel rod 2 are made of the same material, it is beneficial to ensure the normal electrolytic performance of the cathode carbon block 1 as a whole.

[0043] In this embodiment,

[0044] Working principle:

[0045] The copper core 11 is inserted into the embedding groove 3 through the threaded connection groove 9, and then the threaded pressure rod 8 is threadedly connected to the threaded connection groove 9. The threaded pressure rod 8 will continuously squeeze and deform the copper core 11 during its downward movement. The deformed copper core 11 will fill the gap left between the copper core 11 and the embedding groove 3 until the copper core 11 no longer extends into the threaded connection groove 9, that is, the copper core 11 is completely embedded in the embedding groove 3, so that the copper core 11 fits tightly in the steel rod 2, and finally the steel rod 2 with the copper core 11 and the end cover 4 is inserted into the mounting groove 10 of the cathode carbon block 1.

[0046] in:

[0047] 1. Semi-graphite cathode carbon block: Through a large amount of data analysis of domestic and foreign companies using semi-graphite cathode carbon blocks, after using semi-graphite cathode carbon blocks, the cell life is extended, the furnace bottom pressure drop is significantly reduced, the furnace is regular and stable, and the current distribution in the cell is uniform, making the production management of the electrolytic cell more convenient, and the electrolytic cell can produce more aluminum, which is also a reason for the improvement of current efficiency. Secondly, the voltage drop at the bottom of the cell is an important indicator of aluminum electrolysis production. Semi-graphite cathode carbon blocks have a smaller specific resistance, which makes the cell bottom voltage drop, that is, the furnace bottom pressure drop, of the electrolytic cell using the carbon block lower. Experiments have shown that the furnace bottom pressure drop of the electrolytic cell using semi-graphite cathode carbon blocks is 50-60mv lower than that of the electrolytic cell using ordinary carbon blocks. It can be seen that the application of semi-graphite cathode carbon blocks is an important way to reduce the furnace bottom pressure drop and save energy and reduce consumption.

[0048] 2. Copper-embedded cathode steel bar: By embedding a certain amount of copper in a specific position of the cathode steel bar to improve its conductivity, reduce the furnace bottom pressure drop, make the cathode surface current density distribution more uniform, reduce the horizontal current, improve the MHD stability, and also reduce the aluminum liquid flow rate, which has a positive impact on the current efficiency. At the same time, it increases the service life of the cathode carbon block. The increased MHD stability creates conditions for compressing ACD without losing current efficiency. Copper-embedded cathode steel bars are the preferred choice for reducing the voltage of the electrolytic cell and reducing the DC power consumption per ton of aluminum.

[0049] 3. Assembly of phosphorus pig iron casting cathode: The copper-embedded cathode steel rod and semi-graphite cathode carbon block are preheated with a special heating device. The final heating temperature of the steel rod is not less than 600℃, and the average temperature of the carbon block is not less than 400℃ (the lowest temperature is not less than 300℃). The temperature deviation of each group of cathode steel rods and cathodes does not exceed 50℃. The phosphorus pig iron composition is formulated according to the optimal composition determined by the previous test. While ensuring that the phosphorus pig iron has good fluidity, it can also reduce the iron-carbon pressure drop after assembly. The temperature of phosphorus pig iron out of the furnace is 1450±50℃, and the casting temperature of phosphorus pig iron should not be lower than 1400℃. The molten iron should be fully slaged and desulfurized before pouring. When casting phosphorus pig iron, choose a suitable pouring point and casting speed to ensure that the molten iron can fill the gap between the carbon block and the steel rod at one time and reduce the casting pores. After the cathode group is cooled for 24 hours after casting, the middle of the dovetail groove, i.e. the middle area of ​​the steel bars on both sides, is rammed with cold rammed steel rod paste. The ramming is carried out in six layers, and the ramming density does not exceed 1.5g / cm3. After the cathode group is cooled, the end surface of the carbon block is brushed with silicon carbide fireclay slurry on the 100mm long steel bar (including the top surface and the two side surfaces). It is required to be evenly brushed more than 5 times in the area where the cathode steel bar needs to be insulated, and the thickness of the insulation layer is required to reach about 2mm. The moisture content of silicon carbide fireclay for insulation must be strictly controlled, and it must be cured and dried for more than 24 hours after brushing to achieve the purpose of mud molding and reduce moisture.

[0050] 4. Test of cathode group iron-carbon voltage drop: The test is carried out twice using a voltage drop tester with a current of 100A. The first test is carried out 24 hours after the carbon block is cast and before the cathode group is turned over. During the test, the temperature of the cathode group should be close to room temperature. Each steel rod is tested at 3 points (near end, middle end and far end). The average value of the test results should not exceed 25mV in principle. The second test is carried out after the cathode group is turned over. Since phosphorus pig iron inevitably shrinks after cooling, some steel rods will inevitably loosen after turning over, but this will not have a significant impact on the voltage drop of the cathode group under working conditions. Therefore, the voltage drop value of the secondary test is not required in principle, and can be used as one of the references for the installation and arrangement of the upper slot of the cathode group.

[0051] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An energy-saving copper-embedded cathode carbon block assembly for aluminum electrolysis, comprising a cathode carbon block (1) and a steel rod (2), wherein a mounting groove (10) is formed on the surface of the cathode carbon block (1), and the steel rod (2) is embedded in the mounting groove (10), characterized in that: An embedding groove (3) is provided inside the steel rod (2), and a copper core (11) is provided inside the embedding groove (3); The end of the steel rod (2) is provided with a threaded connection groove (9) which communicates with the embedding groove (3). The end of the steel rod (2) is provided with an end cover (4). A threaded sealing sleeve (7) and a threaded pressure rod (8) are fixed inside the end cover (4). The threaded pressure rod (8) is located inside the threaded sealing sleeve (7).

2. The energy-saving copper-embedded cathode carbon block assembly for aluminum electrolysis according to claim 1, characterized in that: The inner diameters of the embedding groove (3) and the threaded connection groove (9) are equal.

3. The energy-saving copper-embedded cathode carbon block assembly for aluminum electrolysis according to claim 1, characterized in that: The threaded pressure rod (8) is threadably matched with the threaded connection groove (9).

4. The energy-saving copper-embedded cathode carbon block assembly for aluminum electrolysis according to claim 1, characterized in that: An annular thread sealing groove (5) is formed at the end of the steel rod (2). The thread sealing groove (5) is located outside the thread connection groove (9). The thread sealing sleeve (7) is thread-matched with the thread sealing groove (5).

5. The energy-saving copper-embedded cathode carbon block assembly for aluminum electrolysis according to claim 1, characterized in that: The end cover (4) is provided with operation holes (6) on all four sides thereof.

6. The energy-saving copper-embedded cathode carbon block assembly for aluminum electrolysis according to claim 1, characterized in that: The cathode carbon block (1) is made of semi-graphitized carbon.

7. The energy-saving copper-embedded cathode carbon block assembly for aluminum electrolysis according to claim 1, characterized in that: The end cover (4), the threaded sealing sleeve (7), the threaded pressure rod (8) and the steel rod (2) are made of the same material.